The Relevance of the Islamic Financial System in the Light of Inflation: Essence and Paradigm - Ahmad Mahfudzi Mafrudlo; Zuhratul Aini Mansur; Ghilmanul Wasath; Yadi Janwari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Every monetary policy should always be concerned with maintaining a stable and sustainable economy because it is the achievement of every nation. On the other side, efforts to control inflation are based on basic planning and strategies aimed at significant economic growth. The purpose of this research is to identify the basics of the problem of inevitable inflation. starting with the relevance of the Islamic financial system in dealing with inflation in each country, so that the framework and paradigm of economic stability and the Islamic financial system are found. This study is qualitative and uses the descriptive analysis method. According to the research results, it was found that inflation cannot be eliminated; in reality, it can only be minimized into stable inflation. It was found that the reality of the instability of the Islamic financial system has an impact on economic stability. So, it takes a framework and widespread awareness of inflation, including how political implementation, increased human resources, and technological potential affect inflation, as well as mapping all problems so that the budget program anticipates the problem. On the other hand, it is necessary to understand the paradigm of stability in the Islamic financial system, which consists of four aspects: behavioral aspects, political aspects, economic aspects, and social aspects.